Enhanced Dynamic Behaviour of Grid Connected Wind Farms in Load Participation and Frequency Regulation - Okedu, Kenneth E.; Barghash, Hind F. A. (Frontiers in Energy Research, 2021)
The control of grid frequency in power systems due to the penetration of wind turbines is very vital, in order to maintain stability of power grids, based on recent grid requirements. In this paper, the dynamic behaviour of a wind farm connected to an existing grid is presented. The existing grid is made of steam turbines, while the wind farm is based on squirrel cage induction generators. An energy capacitor system is used to stability the wind farm during periods of wind speed change. Loads of various capacities were connected to the grid, in order to test the robustness of the controllers of the energy capacitor system employed. Furthermore, the effect of varying the time constant of the in-built DC-DC chopper of the energy capacitor system was investigated, considering load participation in the grid. One of the targets of this paper is the stabilization of the grid frequency of the network, despite the load capacity and the nature of wind speed in the wind farm. The system performance was evaluated using Power System Computer Design and Electromagnetic Transient Including DC (PSCAD/EMTDC). The same conditions of operation were used in investigating the various scenarios considered in this study, for effective comparison. The natural wind speed employed was the same for all the considered scenarios. The presented results show that small load capacity with high value of low pass filter time constant, gave better response of the grid frequency and the entire variables of the power network.